1995
DOI: 10.2135/cropsci1995.0011183x003500010015x
|View full text |Cite
|
Sign up to set email alerts
|

Xenia and Maternal Effects on Maize Agronomic Traits at Three Plant Densities

Abstract: Kernel mass is a primary yield component in maize (Zea mays L.) governed by both xenia and maternal effects. Because kernel growth depends on assimilate supply, we wanted to learn if kernel-weight genes also affect plant size and agronomic characters. We reciprocally crossed three strains known to differ for rates of grain filling [high (HC), random (RC), and low (LC) R-nj color] with two kernel-weight strains [large (LG), and small (SM)] to produce 12 hybrid strains. For 2 yr at two locations, we grew plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A comparative study of commercial hybrids introduced from 1930 to 2001 showed an average increase in grain yield of 0.09 Mg ha -1 yr -1 (based on year of introduction of the hybrid) when hybrids were compared at 7.9 plants m -2 versus an average increase of only 0.014 Mg ha -1 yr -1 when hybrids were compared at 1.0 plants m -2 (Duvick, 2005). Numerous authors have examined the effect of plant density on relative differences among hybrids and other types of maize cultivars (Bavec and Bavec, 2002;Brekke et al, 2011aBrekke et al, , 2011bCarena and Cross, 2003;Carlone and Russell, 1987;Duvick, 2005;Duvick et al, 2004;Gonzalo et al, 2010;Russell, 1974Russell, , 1984Russell, , 1986Russell, , 1991Sangoi et al, 2002;Seka and Cross, 1995;Singh et al, 2011;Tollenaar, 1992;Widdicombe and Thelen, 2002). However, in few of the cited papers have environmental effects and genotype ´ environment interactions (G ´ E) for density response been addressed in great detail.…”
Section: Researchmentioning
confidence: 99%
“…A comparative study of commercial hybrids introduced from 1930 to 2001 showed an average increase in grain yield of 0.09 Mg ha -1 yr -1 (based on year of introduction of the hybrid) when hybrids were compared at 7.9 plants m -2 versus an average increase of only 0.014 Mg ha -1 yr -1 when hybrids were compared at 1.0 plants m -2 (Duvick, 2005). Numerous authors have examined the effect of plant density on relative differences among hybrids and other types of maize cultivars (Bavec and Bavec, 2002;Brekke et al, 2011aBrekke et al, , 2011bCarena and Cross, 2003;Carlone and Russell, 1987;Duvick, 2005;Duvick et al, 2004;Gonzalo et al, 2010;Russell, 1974Russell, , 1984Russell, , 1986Russell, , 1991Sangoi et al, 2002;Seka and Cross, 1995;Singh et al, 2011;Tollenaar, 1992;Widdicombe and Thelen, 2002). However, in few of the cited papers have environmental effects and genotype ´ environment interactions (G ´ E) for density response been addressed in great detail.…”
Section: Researchmentioning
confidence: 99%
“…While Widdicombe and Thelen (2002) found an increase in test weight at high density, the increase was small, suggesting any impact of density was minimal. Seka and Cross (1995) found a linear response of grain moisture to increasing density, and Widdicombe and Thelen (2002) found a decrease in moisture at higher plant densities. However, Carena and Cross (2003) did not find an effect of plant density on grain moisture.…”
mentioning
confidence: 94%
“…are theoretically determined by both maternal (nuclear and cytoplasmic) and zygotic (embryo and endosperm) effects. The genetic analyses of reciprocal crosses in several species, including Arabidopsis (Alonso‐Blanco et al ., ), maize (Seka and Cross, ; Zhang et al ., ), wheat (Minhas et al ., ), cotton (Pahlavani and Abolhasani, ), peanut (Hariprasanna et al ., ), sorghum (Mohammed et al ., ), pea (Lemontey et al ., ) and bean (Duc et al ., ; Singh et al ., ), have shown that both maternal and xenia (via zygote) effects have significant roles on seed size/weight. However, the relative importance of maternal and zygotic effects has not been analyzed and thus is unclear in rapeseed, in spite of its fundamental interest and significance in genetic study and breeding.…”
Section: Introductionmentioning
confidence: 99%